Digenetic Trematodes of Indian Marine Fishes - Madhavi, Rokkam (Springer Netherlands, 2018)
This book is the first to explore in detail the systematics and taxonomy of the digenean fauna of fish in Indian marine waters. It includes morphological descriptions of 648 species in 190 genera and 30 families. The figures from the original publications are enhanced and made more attractive. Each description is accompanied by information on hosts and distribution. Digenetic trematodes, usually known as Digeneans, are the most diverse group of metazoan parasites of marine fishes. They are parasitic flatworms (Phylum Platyhelminthes) with a complex life-cycle and as adults inhabit mainly the alimentary system and associated organs, but also occur in the blood, under the scales, in the body cavity and in the gall and urinary bladders. Keys to families, genera and species are provided, except for a few large and controversial genera, where morphological characters are insufficient for identification. Although there is extensive literature on Digeneans, it is scattered and largely in obscure local journals. Bringing together most of the primary literature on the subject, this book provides a primer for further study and a starting point for the use of modern molecular methods for the fauna of this region. Unique in its scope, it is a valuable resource for students, professional parasitologists and ecologists as well as fishery and wildlife biologists.